2018
DOI: 10.1093/alcalc/agy053
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Nature and Extent of Children’s Real-time Exposure to Alcohol Marketing in Their Everyday Lives Using Wearable Cameras: Children’s Exposure via a Range of Media in a Range of Key Places

Abstract: These findings highlight the urgent need to implement strict legislative restrictions on all forms of alcohol marketing to fulfil the World Health Organization Global Alcohol Strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…Scores across the nine channels were summed to create an aggregate score, providing an approximation of total alcohol marketing awareness in the past month. Estimating total volume of awareness, as opposed to breadth across channels, is consistent with other recent alcohol marketing research 42 43…”
Section: Methodssupporting
confidence: 82%
“…Scores across the nine channels were summed to create an aggregate score, providing an approximation of total alcohol marketing awareness in the past month. Estimating total volume of awareness, as opposed to breadth across channels, is consistent with other recent alcohol marketing research 42 43…”
Section: Methodssupporting
confidence: 82%
“…Research suggests that advertising originating from locations licensed for on-site consumption of alcohol constitute an important source of exposure to alcohol advertising among children. For instance, a study quantifying children's exposure to alcohol marketing in New Zealand found that children aged 11 to 13 years old are exposed to an average of 4.5 alcohol promotions per day (excluding within stores, on packaging, and on screens), and 18.7% of this exposure occurred in establishments that sell alcohol for on-site consumption [49]. Our findings suggest that greater restrictions may be needed to protect children and adolescents from promotional activities related to alcohol vending in movie theatre environments.…”
Section: Alcoholmentioning
confidence: 99%
“…While there is no underage drinking depicted in this show, adult drinking is strongly suggestive of exceeding the adult guidelines. Depiction of ubiquitous alcohol consumption through reality TV (and other media: viz: Chambers et al., 2018 ) may serve to normalise excessive consumption for minors and young adult viewers, undermining the messages of health bodies such as the National Health and Medical Research Council. The influence and cumulative effect of the many images of alcohol through reality TV and other forms of media are likely to be significant underlying influences on their perceptions of normal and acceptable drinking behaviours.…”
Section: Discussionmentioning
confidence: 99%